Menarche, pregnancies, and breastfeeding do not modify long-term prognosis in multiple sclerosis. (26th March 2019) - Zuluaga, María I.; Otero-Romero, Susana; Rovira, Alex; Perez-Hoyos, Santiago; Arrambide, Georgina; Negrotto, Laura; Galán, Ingrid; Río, Jordi; Comabella, Manuel; Nos, Carlos; Arévalo, María Jesús; Vidal-Jordana, Angela; et al.
Abstract : Objective: To investigate the effect of menarche, pregnancies, and breastfeeding on the risk of developing multiple sclerosis (MS) and disability accrual using a multivariate approach based on a large prospective cohort of patients with clinically isolated syndrome (CIS). Methods: A cross-sectional survey of the reproductive information of female participants in a CIS cohort was performed. We examined the relationship of age at menarche with the risk of clinically definite MS (CDMS), McDonald 2010 MS, and Expanded Disability Status Scale (EDSS) 3.0 and 6.0. The effect of pregnancy (before and after CIS) and breastfeeding in the risk of CDMS, McDonald 2010 MS, and EDSS 3.0 was also examined. Univariate and multivariate analyses were performed and findings were confirmed using sensitivity analyses and a propensity score model. Results: The data of 501 female participants were collected. Age at menarche did not correlate with age at CIS and was not associated with the risk of CDMS or EDSS 3.0 or 6.0. Pregnancy before CIS was protective for CDMS in the univariate analysis, but the effect was lost in the multivariate model and did not modify the risk of EDSS 3.0. Pregnancy after CIS was protective for both outcomes in univariate and multivariate analyses when pregnancy was considered a baseline variable, but the protective effect disappeared when analyzed as a time-dependent event. Breastfeeding did not modify the risk for the 3 outcomes. Conclusions: These results demonstrate that menarche, pregnancies, and breastfeeding did not substantially modify the risk of CDMS or disability accrual using a multivariable and time-dependent approach.